2008
DOI: 10.1007/s10803-008-0670-7
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Self-recognition in Children with Autism Spectrum Disorder

Abstract: Publisher's copyright statement:The original publication is available at www.springerlink.com Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 35 publications
6
42
0
Order By: Relevance
“…Further supporting this suggestion, studies have shown that children with ASD (both high-functioning and mixed ability) do not significantly differ from age and verbal ability matched comparison children in terms of their ability to recognise delayed video images of themselves (Lind & Bowler, 2009a). Such findings may be taken as evidence of intact (higher-order)…”
Section: Higher-order Self-awareness In Asd: Physical and Psychologicmentioning
confidence: 89%
See 2 more Smart Citations
“…Further supporting this suggestion, studies have shown that children with ASD (both high-functioning and mixed ability) do not significantly differ from age and verbal ability matched comparison children in terms of their ability to recognise delayed video images of themselves (Lind & Bowler, 2009a). Such findings may be taken as evidence of intact (higher-order)…”
Section: Higher-order Self-awareness In Asd: Physical and Psychologicmentioning
confidence: 89%
“…temporally extended physical self-awareness but do not necessarily imply intact (higherorder) temporally extended psychological self-awareness (see Lind & Bowler, 2009a).…”
Section: Higher-order Self-awareness In Asd: Physical and Psychologicmentioning
confidence: 99%
See 1 more Smart Citation
“…However, highlighting that this task measures awa thinking, success on this task is not significantly associated with performance on traditional ToM tasks (Suddendorf, 1999;Zelazo, Sommerville, & Nichols, 1999). Lind and Bowler (2009) found that, amongst participants who displayed live video self-recognition (which 95% of all participants did), 93% (n = 25) of participants with autism and 100% (n = 30) of age-and ability-matched comparison participants passed the delayed video self-recognition task. These results are also reported by Nielsen, Suddendorf, & Dissanayake (2006) who used the same task with highfunctioning children with autism.…”
Section: Recognising Own Bodymentioning
confidence: 96%
“…Since findings from several lines of research suggest that people with ASD can also be responsible for committing criminal acts (see, e.g., Allen et al, 2008;Browning & Caulfield, 2011;Howlin, 1997;Woodbury-Smith et al, 2005;Woodbury-Smith, Clare, Holland & Kearns, 2006), future work is needed to explore how people with ASD who have actually perpetrated the act behave when asked to testify. For example, given the difficulties that people with ASD have in incorporating their concept of the self when recollecting episodic events (e.g., Crane & Goddard, 2008;Crane et al, 2009;Lind, 2010;Lind & Bowler, 2009a, 2010, they may struggle to recall such an event where they played an active causal role, particularly when combined with the increased interrogative pressure of being questioned as a suspect.…”
Section: Future Research Directionsmentioning
confidence: 99%